NUMERICAL MODELING OF THE INTENSE DEFORMED STATE AND PECULIARITIES OF STRUCTURE FORMATION OF CAST IRON AT HOT EXTRUSION MOLDING - A. I. Pokrovsky; P. E. Lushchik (Литьë и металлургия)
The specific features of structure formation of high-strength cast iron subjected to direct extrusion with different strain (ε) are studied both theoretically (by computer modeling) and experimentally (by metallographic analysis using light and electron microscopes). Evolution of the shape of graphite inclusions with increasing ε is examined and the stress-strain state in the vicinity of the graphite inclusion/metal matrix interface is modeled numerically. It is shown that graphite inclusions in the cast iron are deformed plastically even at high strains, up to 80–90%. Scanning electron microscopy has revealed the surface morphology of the deformed graphite inclusions.